Association of lifestyle-related factors with circadian onset patterns of acute myocardial infarction: a prospective observational study in Japan. Issue 6 (6th June 2014) - Edahiro, Ryuya; Sakata, Yasuhiko; Nakatani, Daisaku; Suna, Shinichiro; Usami, Masaya; Matsumoto, Sen; Hara, Masahiko; Kitamura, Tetsuhisa; Sato, Hiroshi; Yamashita, Shizuya; Nanto, Shinsuke; Hikoso, Shungo; et al.
Abstract : Objective: The onset of acute myocardial infarction (AMI) shows characteristic circadian variations involving a definite morning peak and a less-defined night-time peak. However, the factors influencing the circadian patterns of AMI onset and their influence on morning and night-time peaks have not been fully elucidated. Design, setting and participants: An analysis of patients registered between 1998 and 2008 in the Osaka Acute Coronary Insufficiency Study, which is a prospective, multicentre observational study of patients with AMI in the Osaka region of Japan. The present study included 7755 consecutive patients with a known time of AMI onset. Main outcomes and measures: A mixture of two von Mises distributions was used to examine whether a circadian pattern of AMI had uniform, unimodal or bimodal distribution, and the likelihood ratio test was then used to select the best circadian pattern among them. The hierarchical likelihood ratio test was used to identify factors affecting the circadian patterns of AMI onset. The Kaplan-Meier method was used to estimate survival curves of 1-year mortality according to AMI onset time. Results: The overall population had a bimodal circadian pattern of AMI onset characterised by a high and sharp morning peak and a lower and less-defined night-time peak (bimodal p<0.001). Although several lifestyle-related factors had a statistically significant association with the circadian patterns of AMI onset, serum triglyceride levels had the most prominent association with the circadian patterns of AMI onset. Patients with triglyceride ≥150 mg/dL on admission had only one morning peak in the circadian pattern of AMI onset during weekdays, with no peaks detected on weekends, whereas all other subgroups had two peaks throughout the week. Conclusions: The circadian pattern of AMI onset was characterised by bimodality. Notably, several lifestyle-related factors, particularly serum triglyceride levels, had a strong relation with the circadian pattern of AMI onset. Trial registration number: UMIN000004575.